2019
DOI: 10.1155/2019/3719178
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Turner Syndrome Presenting with a 46,XY Karyotype

Abstract: Although Turner syndrome is most commonly associated with a 45,X genotype, other mosaic genotypes are present in approximately half of all cases. We describe a case of Turner syndrome with a 46,XY genotype by conventional 5-cell karyotype who was subsequently found to have a mosaic genotype of 18% 45,X and 82% 46,XY by 50-cell FISH analysis. Individuals with a mosaic 45,X/46,XY genotype have a variety of phenotypic presentations ranging from male to female which are not correlated with the percentage of mosaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…Rasouli et al reported that in cases where conventional karyotype results do not closely match the clinical presentation, FISH analysis with interphase cells may be informative for mosaicism [ 18 ]. Therefore, we additionally performed the FISH analysis and the cheek swab examinations during the same time as the G-band analysis; however, both examinations also revealed 100% 45, X.…”
Section: Discussionmentioning
confidence: 99%
“…Rasouli et al reported that in cases where conventional karyotype results do not closely match the clinical presentation, FISH analysis with interphase cells may be informative for mosaicism [ 18 ]. Therefore, we additionally performed the FISH analysis and the cheek swab examinations during the same time as the G-band analysis; however, both examinations also revealed 100% 45, X.…”
Section: Discussionmentioning
confidence: 99%
“…All life junctures are vulnerable to genetic mosaicism but the early stages of development are more susceptible to mosaicism because cellular proliferation rates are quite high, whereas DNA repair capabilities diminish in the later stages of life. 6 During an embryonic stage, some mutations are proven fatal during initial developmental periods, especially during the period of organogenesis, increasing the probability of clonal expansion and the detrimental effect on phenotype. 7 In genetic mosaicism, mutations can affect a single base to large DNA rearrangements, which can involve a few or thousands of bases to the whole of the chromosome.…”
Section: How a N D When It Happens?mentioning
confidence: 99%
“…According to preimplantation genetic diagnosis international society (PGDIS) guidelines, during ART embryo transfers mosaic trisomies 1,3,4,5,6,8,9,10,11,12,17,19,20,22, X, and Y should be favored over mosaic trisomies 2, 7, 13, 14, 15, 16, 18, and 21. This is may be because the latter group of trisomies carries the known risks of syndromes like Patau syndrome and Down syndrome.…”
Section: Pgdis Guidelinesmentioning
confidence: 99%
“…The main presentation of patients with 45,X/46,XY mosaicism is mixed gonadal dysgenesis (MGD), but they may have different phenotypes depending on the percentage distribution of mosaicism in gonadal tissues and blood. These phenotypes include normal female, TS, genital ambiguity, and male phenotype [5].…”
Section: Introductionmentioning
confidence: 99%